Evaluating the Effects of Subnormothermic Perfusion with AP39 in a Novel Blood-Free Model of Ex Vivo Kidney Preservation and Reperfusion - Juriasingani, S.; Jackson, A.; Zhang, M.Y.; Ruthirakanthan, A.; Dugbartey, G.J.; Sogutdelen, E.; Levine, M.; Mandurah, M.; Whiteman, M.; Luke, P.; Sener, A. (International journal for molecular sciences, 2021)
The use of blood for normothermic and subnormothermic kidney preservation hinders the translation of these approaches and promising therapeutics. This study evaluates whether adding hydrogen sulfide donor AP39 to Hemopure, a blood substitute, during subnormothermic perfusion improves kidney outcomes. After 30 min of renal pedicle clamping, porcine kidneys were treated to 4 h of static cold storage (SCS-4 ◦C) or subnormothermic perfusion at 21 ◦C with Hemopure (H-21 ◦C), Hemopure + 200 nM AP39 (H200nM-21 ◦C) or Hemopure + 1 µM AP39 (H1µM-21 ◦C). Then, kidneys were reperfused with Hemopure at 37 ◦C for 4 h with metabolic support. Perfusate composition, tissue oxygenation, urinalysis and histopathology were analyzed. During preservation, the H200nM-21 ◦C group exhibited significantly higher urine output than the other groups and significantly higher tissue oxygenation than the H1µM-21 ◦C group at 1 h and 2h. During reperfusion, the H200nM-21 ◦C group exhibited significantly higher urine output and lower urine protein than the other groups. Additionally, the H200nM-21 ◦C group exhibited higher perfusate pO2 levels than the other groups and significantly lower apoptotic injury than the H-21 ◦C and the H1µM-21 ◦C groups. Thus, subnormothermic perfusion at 21 ◦C with Hemopure + 200 nM AP39 improves renal outcomes. Additionally, our novel blood-free model of ex vivo kidney preservation and reperfusion could be useful for studying other therapeutics.
Research Article
Keywords: kidney preservation; kidney transplantation; hydrogen sulfide (H2S); AP39; donation after cardiac death (DCD); subnormothermic